1999
DOI: 10.1177/002224379903600407
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Household State Dependence Effects across Categories

Abstract: Brand choices over time are dictated not just by households' intrinsic brand preferences, but also by marketing variables and state dependence effects. The authors examine brand choice behavior across five product categories as a function of these variables. Choice within a category is modeled with a multinomial probit model. A Bayesian variance components approach is used to model the covariation of household response parameters across categories. The model enables the authors to identify similarities in hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
90
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(99 citation statements)
references
References 39 publications
6
90
2
1
Order By: Relevance
“…We¯nd strong evidence for state dependence in store mobility. This result complements earlier work on brand choice (e.g., Keane 1997) and cross-category purchasing behavior (e.g., Seethuraman et al, 1999). The longer a shopper continues with the current main store, the less likely the shopper will transition away to another main store.…”
supporting
confidence: 80%
“…We¯nd strong evidence for state dependence in store mobility. This result complements earlier work on brand choice (e.g., Keane 1997) and cross-category purchasing behavior (e.g., Seethuraman et al, 1999). The longer a shopper continues with the current main store, the less likely the shopper will transition away to another main store.…”
supporting
confidence: 80%
“…However, it is an empirical question as to whether or not state dependence is an important force in our data. With a normal distribution of heterogeneity, a number of authors have documented that positive state dependence is present in consumer packaged goods panel data (see, for example, Seetharaman, Ainslie, and Chintagunta, 1999). However, there is still the possibility that these results are not robust to controls for heterogeneity using a flexible or nonparametric distribution of preferences.…”
Section: Inertia As Structural State Dependence Versus Spurious Stmentioning
confidence: 99%
“…□Brand‐specific state dependence In the basic utility specification , state dependence is captured by a parameter that is constrained to be identical across brands. Several authors have found the measurement of state dependence to be difficult (see, for example, Keane, 1997; Seetharaman, Ainslie, and Chintagunta, 1999; Erdem and Sun, 2001) even with a one‐component normal model for heterogeneity. The reason for imposing one state dependence parameter could simply be a need for greater efficiency in estimation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The vector Z h contains observable demographic characteristics of the households that affect the household specific response parameters (Seetharaman, Ainslie, & Chintagunta, 1999;Hansen, Singh, & Chintagunta, 2006). The latent term l h accounts for effects of other household-specific characteristics such as time constraints of the households that are not directly observed.…”
Section: Model Developmentmentioning
confidence: 99%